Impact of caffeine on heart rate and blood pressure at rest and during exercise - Azam Mousavi; Maryam Koushki Jahromi; Mohsen Salesi; Farhad Daryanoush; Ebrahim Khoshnam; Asghar Nikseresht; Ebrahim Hemati (فصلنامه دانشگاه علوم پزشکی جهرم, 2011)
Introduction:Several studies have evaluated the impact of caffeine consumption on athletes performance from different aspects; however, the findings are varied. The aim of this research was to evaluate the impact of caffeine consumption on some of the cardiovascular factors including heart rate and blood pressure at rest, at the end of exercise, and during the 3rd and 5th minutes of recovery. Material and Methods:The subjects of this study included 20 female athletes, voluntarily participating in the study. Two separate tests with an interval of one week were conducted. The subjects received placebo for the first test and caffeine containing capsules (5 mg/kg) for the second test. The patient heart rate and blood pressure were measured at rest, at the end of the exercise and during the 3rd and 5th minutes of recovery after submaximal test. Maximal oxygen consumption (VO2max) was measured using Fax submaximal cardiorespiratory test. Paired t- test was used for data analysis. Results:Caffeine consumption had no significantly effect on VO2max, resting and end exercise heart rate, and blood pressure recorded at the end of the exercise. Caffeine consumption caused a significant increase in the heart rate during 3rd and 5th minutes of recovery, and in blood pressure at rest, and during the 3rd and the 5th minutes of recovery in the athletes. Conclusion:Due to the caffeine induced increase in blood pressure and heart rate, caffeine consumption (5 mg/kg) before submaximal exercise is not recommended either for those who suffer hypertension or cardiac disease nor for those who do exercise for health or athletic purposes.